Functional Two-Dimensional Coordination Polymeric Layer as a Charge Barrier in Li–S Batteries - Huang, Jing-Kai; Li, Mengliu; Wan, Yi; Dey, Sukumar; Ostwal, Mayur; Zhang, Daliang; Yang, Chih-Wen; Su, Chun-Jen; Jeng, U-Ser; Ming, Jun; Amassian, Aram; Lai, Zhiping; et al. (ACS nano, 2018)
Ultrathin two-dimensional (2D) polymeric layers are capable of separating gases and molecules based on the reported size exclusion mechanism. What is equally important but missing today is an exploration of the 2D layers with charge functionality, which enables applications using the charge exclusion principle. This work demonstrates a simple and scalable method of synthesizing a free-standing 2D coordination polymer Zn2(benzimidazolate)2(OH)2 at the air–water interface. The hydroxyl (−OH) groups are stoichiometrically coordinated and implement electrostatic charges in the 2D structures, providing powerful functionality as a charge barrier. Electrochemical performance of the Li–S battery shows that the Zn2(benzimidazolate)2(OH)2 coordination polymer layers efficiently mitigate the polysulfide shuttling effects and largely enhance the battery capacity and cycle performance. The synthesis of the proposed coordination polymeric layers is simple, scalable, cost saving, and promising for practical use in batteries.